Carotid artery stenting has similar outcomes in men and women - Ansuategui, Marina (J Vasc Bras, 2021)
BACKGROUND: The aim of carotid interventions is to prevent cerebrovascular events. Endovascular treatment (carotid-artery-stenting/CAS) has become established as an alternative to open surgery in some cases. Historically, female sex has been considered as a perioperative risk factor, however, there are few studies regarding this hypothesis when it comes to CAS. OBJECTIVES: To analyze the CAS results in our center adjusted by sex. METHODS: A retrospective cohort study was designed, including patients with carotid atheromatosis operated at a single center from January 2016 to June 2019. Our objective was to compare cardiovascular risk, including myocardial infarction, stroke, and mortality, by sex. Follow-up rates of stent patency, restenosis, stroke, myocardial infarction, and death were reported. RESULTS: 71 interventions were performed in 50 men (70.42%) and 21 women (29.57%). Mean age was 70.50 ± 10.72 years for men and 73.62 ± 11.78 years for women. Cardiovascular risk factors did not differ significantly between sexes. Mean follow-up was 11.28 ± 11.28 months. There were no significant differences in neurological events during follow-up. No adverse cardiological events were detected at any time. Regarding the mortality rate, during medium-term follow up there were 2 neurological related deaths with no significant differences between sexes (p=0.8432). Neither sex had higher rated of restenosis during long term follow-up (5.63% vs. 1.41%, p = 0.9693) or reoperation (1.41% vs. 1.41%, p = 0.4971). All procedures remained patent (<50% restenosis). CONCLUSIONS: Despite the limitations of our study, CAS is a therapeutic option that is as effective and safe in women as in men. No sex differences were observed.